PENGARUH BUDAYA ORGANISASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PADA PT PRIMA INDONESIA LOGISTIK - Jenni Kristina Br Panjaitan; Emma Novirsari; Ahmad Fadli (MTU PRESS, 2023)
This study aims to determine the influence of training and organizational culture on employee career development at PT Prima Indonesia Logistics. The population of this study was 60 employees and a sample of 30 people using a saturated sampling technique. The data collection technique used was through questionnaires whose measurements were with a Likert scale and processed statistically using multiple regression analysis and hypothesis testing t test, f test, and determinant coefficient. From data analysis for each variable, the multiple regression equation Y = 12.955 + 0.362x_1 + 0.261x_2 + e. The Adjusted R Square value was obtained at 0.309, which means that X1 and The partial test produced by each independent variable has a positive effect on the dependent variable with a research significance of less than 0.05 so that the hypothesis is accepted, and the result of the simultaneous test calculation is 14,656 with f table 3.11, which means Fcount > Ftable with a level of significance ( α) 0.000 < 0.05, which means the hypothesis is accepted, namely that training and achievement simultaneously have a significant effect on employee performance at PT. Prima Indonesia Logistics